Physiochemical property changes and mineral element migration behavior of bamboo shoots during traditional fermentation process. Issue 10 (10th August 2020) - Chi, Hai; Lu, Wangwei; Liu, Guoqin; Qin, Yuyue
Abstract: The pH value, color, microbial property, texture, microstructure, and mineral element migration behavior of bamboo shoot ( Dendrocalamus latiflorus ) during traditional fermentation process were studied for 42 days to evaluate the effect of such processing method on its physiochemical properties. The result revealed that pH value of the fermentation broth and the textural property of bamboo shoots, gradually decreased during the fermentation process. The SEM analysis indicated that the cell wall began to collapse and the cell structure was damaged on day 28. The content of selenium, iron, and manganese before fermentation was 57.5, 6.84, and 2.87 mg/kg, respectively, and on day 30, decreased to 29.4, 3.87, and 1.13 mg/kg, respectively. The trend in mineral element migration during fermentation was accordance with changes in sensory quality, hardness, chewability, and cohesion of bamboo shoots. The study could provide potential references for quality control of fermented bamboo shoot as health enhancing food. Practical applications: Fermented bamboo shoot is a kind of favorite food in China. During fermentation, the physiochemical property and mineral element content gradually changed. The best compromise between pH value, color, microbial property, microstructure, texture, and mineral element migration could be achieved by modulating the fermentation conditions. The research result provided guideline for quality control of fermented bamboo shoot and improvement of fermentation technique.